Molecular Composition of and Potential Health Benefits Offered by Natural East African Virgin Sunflower Oil Products: A 400 MHz 1H NMR Analysis Study - Benita, Percival; Etienne, Savel; Gilbert, Ampem; Miles, Gibson; Mark, Edgar; Fereshteh, Jafari; Katy, Woodason; Kianna, Frederick; Philippe, Wilson; Martin, Grootveld (International Journal of Nutrition, 2019)
Objectives: Sunflower oil (SFO) is regularly employed for cosmetic, emollient and food frying purposes, the latter representing its foremost use globally. Therefore, full investigations of the molecular composition and quality of SFO products are a major requirement. In this study high-field 1H NMR analysis was employed to explore the molecular composition and authenticities of East African virgin (EAV) SFO products, particularly their acylglycerol fatty acid contents, together with those of selected minor constituents. Results acquired were statistically compared to those obtained on commercially-available, EU-approved refined SFO products via NMR-linked multivariate chemometrics strategies. Methodology: High-field 1H NMR spectra of EAV and refined SFOs (n = 55 and 4 respectively) were acquired at an operating frequency of 400 MHz. Their triacylglycerol fatty acid, triacylglycerol hydrolysis product, and sterol and stanol contents were determined via intelligent frequency bucketing and electronic integration of selected resonances. Univariate analysis-of-variance, and multivariate ROC curve evaluations were conducted to determine the magnitude and statistical significance of analyte concentration differences between these two sample classifications. Further multivariate NMR-linked chemometrics analyses such as principal component, random forest and support vector machine classification analyses were also utilised for this purpose. Key Results: Multicomponent 1H NMR analysis demonstrated that EAV SFOs had significantly higher and lower contents of monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs), respectively, than those of refined SFOs. Furthermore, significantly higher concentrations of ‘health-friendly’, cholesterol-blocking sterols and stanols were also found in these virgin SFO products. Major Conclusions: 1H NMR analysis provides much valuable molecular information regarding the composition and virginal status of SFOs.The high [MUFA]:[PUFA] content ratio of unrefined EAV SFO products renders them more suitable and safer for commercial or domestic deep-frying episodes than refined SFOs (MUFAs are much more resistant to thermally-induced peroxidation than PUFAs). These products also potentially offer valuable health benefits in view of their high natural sterol and stanol contents.
Keywords: Virgin Sunflower Oil; East Africa; 1H NMR Analysis; NMR-Based Chemometrics Analysis; Triacylglycerols; Diacylglycerols and Monacylglycerols; Monounsaturated Fatty Acids; Polyunsaturated Fatty Acids; Sterols and Stanols; Lipid Oxidation Products.